Formulasi Pemidanaan Pelaku Tindak Pidana Pornografi Siber berdasarkan Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Kedua atas Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Satrio, Bagus; Rahmat, Diding; Sudarto, Sudarto (Neolectura, 2025)
One type of crime that is growing rapidly through the internet is the distribution of pornographic material, known as cyberporn. To find pornographic sites or cyberporn on the internet, users can search on certain computer networks. Websites that provide pornographic content are deliberately created by site owners to provide pornographic images or videos to users. This will certainly have a negative impact on users. The research method is normative juridical. The results of the study are Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions that refers to the principle of lex specialist derogate legi generalis which means that special law overrides general law, so here the Criminal Code can be overridden by the Pornography Law and the ITE Law. The formulation of the Panel of Judges' Considerations in Decision Number 290/Pid.Sus/2020/PT.DKI Reviewed from the Perspective of Legal Objectives has not been maximized, considering that the criminal sanctions in Article 45 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions state that it is punishable by imprisonment for a maximum of 6 (six) years and/or a maximum fine of Rp1,000,000,000.00 (one billion rupiah). Basically, the ITE Law can ensnare cyberporn, but the problem is in the guidelines for sentencing and the limitations of human resources and technology in enforcing the law against cyberporn perpetrators by law enforcement officers.